Support employment of parsons the immobile age in province Łódzkie - Wiktorowicz, Justyna; Kołodziejczyk-Olczak, Izabela (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
Ageing of societies is one of the most serious problems facing modern Europe. Poland belongs to countries relatively young demographically, however in the twenty-year perspective the situation in this area will undergo the significant deterioration. These problems will be particularly outlined in the voivodeship of Lodz, where at present/already the share of people at retirement age is very high and persons in the immobile working age are characterized by low economic activity. This/Such a situation requires a wider/broader implementation of support policy adapted to the needs of people aged 45+. Activities in this field are conducted/carried out in the region of Lodz especially in the new financial perspective 2007-2013. This action is trying to meet the assumptions of the Program "Solidarity across Generation. Measures aiming at increasing the economic activity of people aged 50+". The purpose of this study is the assessment/evaluation of activities addressed to people 45+ which are undertaken in the voivodeship of Lodz (especially within the confines of the European Social Fund assets as well as /and national resources). In this work were used the results of the study carried out in the project "Equalising Opportunities on the Labour Market for people aged 50+", conducted by the Human Resource Development Centre and University of Lodz.